a) (+2).(+4).(+5). (+3) =
b) (-2).(-3).(+6). (-1) =
c) (+4).(+8).(-2).(-3) =
d) (-10).(-1).(-2).(-1) =
e) (-20).(-2). (0). (+1) =
Respostas
respondido por:
5
Explicação passo-a-passo:
a) (+2).(+4).(+5) .(+3)= (+8).(+5).(+3)= (+40).(+3)= +120
b) (-2).(-3).(+6).(-1)= (+6).(+6).(-1)=(+36).(-1)= - 36
c) (+4).(+8).(-2).(-3)= (+32) .(-2).(-3)= (-64) .(-3)= + 192
d) (-10).(-1).(-2).(-1)= (+10).(-2).(-1)= (-20).(-1)= +20
e) (-20).(-2).(0).(+1)= (-40).(0).(+1)= 0.(+1)=0
Na multiplicação sinais iguais resposta positiva e sinais diferentes resposta negativa
Perguntas similares
5 anos atrás
5 anos atrás
5 anos atrás
8 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás